Analysis of Project-Based Blended Learning in Statistics Learning in Higher Education (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to analyze the results of the application of Blended Learning which refers to the Project-Based Learning (PjBL) model. Blended Learning and PjBL can be packaged as a learning model, namely Project-Based Blended Learning (PjB2L). The design of learning activities with the help of Bina Sarana Informatika University elearning online media (MyBest) is used to measure its impact on student learning outcomes in Statistics courses. The focus of this study describes two main things, namely the description of the application of statistics lectures with the PjB2L model and the results of statistical tests regarding differences in learning outcomes obtained. Quasi-experimental research was designed to measure the comparison of student learning outcomes in experimental classes (with the PjB2L model) and control classes (conventional/blended direct learning). The 100 students involved in this study were divided into two classes, namely the control class which included 50 students and the experimental class which involved 50 students. In addition, in the data analysis technique, analysis of covariance (ANACOVA) was used to compare the results of the control group and the experimental group, with the covariance variable being the pre-test result (initial knowledge). The results showed significant differences. The difference shown in this study leads to the support of better learning outcomes of the experimental group